2019
DOI: 10.1371/journal.pone.0226941
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the utility and repeatability of the renal resistive index in horses

Abstract: The aim of this study was to establish the value of the renal resistive index (RI) of intrarenal arteries in healthy warmblood non-racing horses of different ages to assess the influence of physiologic factors and repeatability of measurement. The kidney ultrasonography examination was performed in three age groups: 15 foals, 15 adults and 15 elderly horses. The procedure was performed in unsedated standing animals. RI values were measured using pulsed-wave Doppler at the medial part of each kidney in the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 35 publications
3
26
1
Order By: Relevance
“…As far we are aware, this is the first report describing normal RI values for cattle, and therefore, there is no information available in the scientific literature with which to compare our results. Our findings are consistent with those of other studies, in humans [ 34 , 35 ], in healthy dogs and cats [ 12 , 36 ], donkeys [ 24 ], and horses [ 33 ] that did not find any differences between the right and left kidney in physiological conditions, although other studies have reported differences in horses [ 24 , 25 ] and cats [ 9 ]. Although it is difficult to explain this difference, more data must be collected to determine whether the difference is due to technical or anatomical variants.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…As far we are aware, this is the first report describing normal RI values for cattle, and therefore, there is no information available in the scientific literature with which to compare our results. Our findings are consistent with those of other studies, in humans [ 34 , 35 ], in healthy dogs and cats [ 12 , 36 ], donkeys [ 24 ], and horses [ 33 ] that did not find any differences between the right and left kidney in physiological conditions, although other studies have reported differences in horses [ 24 , 25 ] and cats [ 9 ]. Although it is difficult to explain this difference, more data must be collected to determine whether the difference is due to technical or anatomical variants.…”
Section: Discussionsupporting
confidence: 93%
“…The limit may be more similar to that in other large animals, but there is no relevant information available in the scientific literature. Recent studies in horses and donkeys [ 24 , 33 ] did not establish a cut-off value, but the RI values were below 0.7 for both kidneys, as in our study. In relation to PI, the value we propose in cattle is much lower than those reported for dogs (1.52) and cats (1.29) [ 12 ].…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations